National Competition Policy: effective stewardship of markets - Fenna, Alan (ANU Press, 2019)
Following the policy assessment framework proposed in the introduction to this volume, this chapter considers the extent to which, and the ways in which, the NCP was an instance of policy success in programmatic, process, political and durability terms. Unlike many other ‘policies’ evaluated in this volume and elsewhere, the NCP was explicitly named as such—formally articulated and documented, with clear definitions and boundaries—making its characterisation and study more straightforward than might otherwise be the case.